International Development Cooperation Today : a Radical Shift Towards a Global Paradigm - Develtere, Patrick; Huyse, Huib; Ongevalle, Jan van (Leuven University Press, 2021)
Over the past 60 years high-income countries have invested over 4000 billion euros in development aid. With varying degrees of success, these investments in low-income countries contributed to tackling structural problems such as access to water, health care, and education. Today, however, international development cooperation is no longer restricted to helping by giving. Instead, it is rather about opportunities, mutual interests, risk taking, and an inclusive societal approach. With the arrival of major new actors such as China, India, and Brazil, and the manifestation of private companies and foundations like the Bill and Melinda Gates Foundation, development aid is being eclipsed by new forms of international cooperation, increasingly accompanied by investments, trade, and give-and-take exchanges.0The agenda for sustainable development, adopted by all United Nations Member States in 2015 and to be realised by 2030, is a case in point of new influential frameworks that usher in a global rather than a traditional North-South perspective.0This book reviews 60 years of international development aid and its relevant actors, outlining today?s challenges and opportunities. Richly illustrated with case studies and examples, 'International Development Cooperation Today' maps successes and failures and synthesizes visions and discussions from all over the world. By pointing out the radical shift from the traditional North-South perspective to a global paradigm, this book is essential reading for all practitioners, academics, and donors involved in development aid.